Not my president: how names and titles frame political figures - Berg, Esther van den; Korfhage, Katharina; Ruppenhofer, Josef; Wiegand, Michael; Markert, Katja (The Workshop on Natural Language Processing and Computational Social Science - proceedings of the Third Workshop, 2019)
Naming and titling have been discussed in sociolinguistics as markers of status or solidarity. However, these functions have not been studied on a larger scale or for social media data. We collect a corpus of tweets mentioning presidents of six G20 countries by various naming forms. We show that naming variation relates to stance towards the president in a way that is suggestive of a framing effect mediated by respectfulness. This confirms sociolinguistic theory of naming and titling as markers of status.